حيدر راضي مالح التأثير التثبيطي لبعض نباتات العائلة المركبة Composite في نمو فطر Erysiphe graminis f.sp. tritici L. المعزول من اوراق نبات الحنطة Triticum aestivum L. وانبات ابواغه - راضيحيدر (University of Thi-Qar Journal of Science, 2019)
This study aimed to examine the activity of aqueaos extract of Helianthus annuus L. , Tagetes patula L. and Artemisia herba_alba L. on spore germination and the growth of Erysiphe graminis f.sp. tritici that isolated from Triticum aestivum L. The results showed that the aqueaos extract of Helianthus annuus L. , Tagetes patula L. and Artemisia herba_alba L. were differed significantly reduced the growth and spore germination of Erysiphe graminis f.sp. tritici , The higher concentration (15%) of all extracts revealed greater inhibition to the fungal growth. Artemisia herba_alba and Tagetes patula aqueaos extracts had a lower and higher percentage of the growth of Erysiphe graminis f.sp. tritic ,were (42.1% ,77.3%) consecutively. Artemisia herba_alba had a lower percentage of the spore germination of Erysiphe graminis f.sp. tritici was (31.1%) , and Helianthus annuus had higher percentage was (71.2% ). The aim of this study is to find out the chemical compound of aqueaos extract of Helianthus annuus L. , Tagetes patula L. and Artemisia herba_alba L. to contain several compound have antifungal activity , It Flavonoids ,Alkaloids and Saponins.